Determination and prediction of the magnetic anisotropy of Mn ions - Duboc, Carole (Chemical Society Reviews, 2016)
EPR spectroscopy combined with quantum chemistry for the investigation of the magnetic anisotropy of MnII, MnIII and MnIV.